Measurement of Country Specific Internationalisation in China: India Study Centre Questionnaire (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The India Study Centre Questionnaire (ISCQ) has been developed to measure the level of internationalisation of higher education (IHE) with reference to India at the India Study centres in China. The concept of IHE has been constructed on the basis of the significantly correlated themes that emerged from the academic research literatures (N=36). The correlation among the emergent themes (N=52) comprising the components of the IHE was tested on the basis of a text analysis. The themes were itemised in accordance with the Ontological or Existentialist, Phenomenological or Instrumentalist, Propositional or Imagistic approaches of conceptualisation with an intent to satisfy the Evaluative or Normative need of the theoretical framework of this study. The designed instrument (ISCQ) devised on the emergent themes was administered on the students (N=28) of India study centre of Peking University, Beijing to test the reliability and validity of the instrument. In order to test and retest the robust validity of the instrument (ISCQ) two more rounds of piloting the questionnaire would be required. Five extensive interviews were conducted with the faculties to validate the structure and content of the ISCQ. However, owing to politico-academic sensitivity, approaching the respondents would need formal consent from the authorities of the institutions in context. Interviews were conducted with five teachers of country specific study centres from prominent institutions.